(900) An Introduction to Simulation مقدمة عن تطبيق الماكاه لاجهزة الكمبيوتر (الحاسوب) الرقمية - El Shafei, Al Walid (INP., 2024)
Simulation, one of the earliest uses of digital computers, remains a critical application across diverse fields. It encompasses various forms, such as making one computer mimic another, studying ballistic missile behavior, or modeling businesses to evaluate management decisions. Engineering extensively utilizes simulation, particularly with analog computers for continuous system dynamics. Applications span traffic flow, message networks, manufacturing operations, computer systems, and supply chains.